Strength Properties of High-Strength Concrete Containing Coal Bottom Ash as a Replacement of Aggregates - In-Hwan Yang; Jihun Park; Nhien Dinh Le; Sanghwa Jung (Advances in Materials Science and Engineering)
Most previous studies on the strength properties of coal bottom ash (CBA) concrete have focused on concrete with a normal compressive strength, and thus, studies on the strength properties of high-strength concrete (HSC) containing CBA are limited. Therefore, the effects of replacing fine aggregates with CBA and variations in the curing age on the strength properties of HSC with a compressive strength of greater than 60 MPa were investigated in this study. The different CBA contents included 25, 50, 75, and 100%, and the different curing ages were 28 and 56 days. The mechanical properties of the HSC with CBA incorporated as fine aggregates were examined. The experimental results revealed that CBA could be partially or totally substituted for fine aggregates during HSC production. The test results also showed that the compressive, splitting tensile, and flexural strengths of the HSC containing CBA fine aggregates slightly decreased as the CBA content increased. Moreover, useful relationships between the compressive strength, splitting tensile strength, and flexural strength were suggested, and the predictions reasonably agreed with the measurements. Compared to those of the control specimen, the pulse velocities of the HSC specimens at various CBA contents decreased by less than 3%. In addition, equations for predicting the strength values of CBA concrete by using the ultrasonic pulse velocity were suggested.